SISTEM INFORMASI RESERVASI PADA âLASECA SALON & SPAâ - , BINTARTI ARIA WARDANI, Nur Rokhman, S.Kom, M.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Laseca Salon and spa is one of business sector in beauty salon which has many treatment services. Treatment management data which do by manually make the worker having some difficulties in making of report and data manipulate. Besides that, the online reservations of treatment which do from some social media also make a problem to, because they canât contact or reached the visitors. To solve the problems of Laseca staffs, Reservation Information System in âLaseca Salon and Spaâ was bulit which able to data processing like processing data of customers, treatment dataâs, and reservation dataâs. The reservation information system in âLaseca Salon dan Spaâ implemented by using MySQL basic data and PHP programming language with CodeIgniter framework. The reservation information system in âLaseca Salon dan Spaâ can be used for processing data of customers, treatment, reservation, making report of transaction and reservation periodically, shows graphic of transaction and reservation periodically or at regular interval, and also can processing online reservation by web.